IMPACT OF NANO AND MINERAL FERTILIZERS ON QUALITY AND MEDICAL PROPERTIES OF FLAX OIL - B. A. Omer,; B. J. Mahmood, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
Two field factorial experiments were carried out at (Grda-rasha and Grdmala) fields in Erbil Governorate - Kurdistan Region-Iraq during the growing season of 2019-2020. This study was aimed to evaluate the effects of Nano and mineral fertilizers on quality and some medical properties of two flaxseed oil (Linum usitatissimum L.) cultivars with a randomized complete block design using 3 replicates. The first factor included seven fertilization treatments (control, Kcl, Urea, Agriculture Sulfur, Triple Super Phosphate, Super Nano-fertilizer, and Nano-NPK), the second factor was Libra and Brazowe flax cultivars. The fertilizer treatments significantly affected natural product properties. The highest value of mucilage (30.70 and 39.26 %) were produced from application of urea and Nano NPK, moreover the highest value of antioxidant activity (75.30 and 86.53 %) was produced from the application of super Nano and triple super phosphate for both locations respectively. The cultivars affected significantly on most of the studied characteristic, the highest mucilage, phenol content and antioxidant activity were produced from the Brazowe cultivar at Grdmala. Application of Nano NPK caused a significant increase in linolenic acid concentration at both locations, which were reached to (39.10 and 37.35 %) respectively. The highest value of oil (33.42 %) had produced from interaction treatments of (Brazowe x Nano NPK) while mucilage, and linolenic were obtained from interaction treatments of (Libra x Nano NPK) with the values of (40.48 and 39.40 %), respectively.